Core-shell NH2-MIL-125-coated Ni (OH) 2 composite photocatalyst rich in anions on surface and preparation method
By generating an amorphous Ni(OH)2 layer on the surface of NH2-MIL-125, forming a core-shell structure with anions rich surface, NH2-MIL-125@Ni(OH)2 composite photocatalyst was prepared, and the existing light was solved The problem of insufficient activity of catalyzing water decomposition of hydrogen under visible light has achieved efficient and stable hydrogen generation.
Patent Information
- Application Number
- CN202411235146.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-02-14
AI Technical Summary
The existing photocatalysts have insufficient activity in catalyzing water decomposition of hydrogen under visible light, and their stability and cost control are poor.
By forming an amorphous Ni(OH)2 layer on the surface of the metal organic framework material NH2-MIL-125, a core-shell structure with anions rich surface was formed, and an NH2-MIL-125@Ni(OH)2 composite photocatalyst was prepared. This method uses methanol as a solvent to react under certain temperature and time conditions to form a composite catalyst with high catalytic properties.
The optimal hydrogen evolution amount under 3 h light was achieved at 807.39 µmol g-1, which was 4 times higher than the original NH2-MIL-125, and the catalyst was reused, and the hydrogen evolution amount was still retained after four cycles. 75.0%. The composite catalyst exhibits efficient hydrogen generation capability in the photocatalytic system.
Smart Images

Figure CN119425794A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich anions on the surface and a preparation method thereof, which is specifically suitable for photocatalytic efficient hydrogen evolution and belongs to the technical field of composite photocatalyst preparation and application. Background Art
[0002] Excessive consumption of fossil energy has caused a global energy crisis and environmental pollution. Solar energy reserves are abundant and pollution-free, but limited conversion efficiency limits its efficient use and storage. In order to meet sustainable development, fixing solar energy in the chemical bonds of high-energy molecules to convert it into chemical energy is the best solution. Hydrogen energy has high energy density, high calorific value and eco-friendliness, making it an ideal substitute for fossil energy. There are many ways to prepare hydrogen, among which the method of photocatalytic water splitting to analyze hydrogen is economical and environmentally friendly. The development of photocatalysts with high catalytic activity is a key research issue.
[0003] In recent years, the use of metal organic framework materials (MOF) as precursors for the preparation of photocatalysts has shown great application prospects. As a type of porous crystalline material with good stability and ultra-high specific surface area, MOF has excellent potential in improving the migration rate of photogenerated carriers and the utilization rate of visible light. Related research has also made certain progress. For example, China's invention patent CN103240130A discloses a TiO2 / MIL-101 composite catalyst and its preparation method and application. The activated MIL-101 is immersed in deionized water and stirred; titanium sulfate and MIL-101 solution are mixed and stirred to dissolve, and urea is added and stirred to obtain a reaction mixture; the reaction mixture is transferred to a high-pressure reactor, and the product is naturally cooled after constant temperature treatment, and the product is washed and centrifuged to obtain a TiO2 / MIL-101 composite catalyst for photocatalytic water decomposition. The composite catalyst is applied to photocatalytic water decomposition, and shows a higher catalytic activity for photocatalytic water decomposition and hydrogen production than TiO2 and MIL-101 alone under ultraviolet visible light, but the photocatalytic activity of TiO2 / MIL-101 under visible light needs to be improved. For example, Chinese invention patent CN113019454A discloses a preparation method and application of NH2-MIL-101(Fe)@NiCoP composite nano-photocatalyst, wherein NH2-MIL-101(Fe) is prepared by FeCl3·6H2O, NH2-BDC and DMF; NH2-MIL-101(Fe) is dispersed in a mixed solution of CoCl2·6H2O and RP by an in-situ deposition method to prepare NH2-IL-101(Fe)@NiCoP composite nano-photocatalyst. The application of the prepared H2-MIL-101(Fe)@NiCoP nano-photocatalyst in the degradation of antibiotic pollutants in water shows efficient photocatalytic activity.
[0004] Therefore, in view of the powerful characteristics of MOF and the principles and methods of photocatalytic hydrogen evolution, it is still urgent to enhance the hydrogen evolution activity of NH2-MIL-125, design a composite photocatalyst with good stability and catalytic performance, and efficiently decompose water to generate hydrogen and further broaden its application field. Summary of the invention
[0005] In order to solve the problems existing in the background technology, the purpose of the present invention is to provide a composite photocatalyst having good stability, capable of enhancing the hydrogen evolution activity of NH2-MIL-125, and capable of efficiently decomposing water to generate hydrogen, and a preparation method thereof. The prepared catalyst can effectively photocatalytically decompose water to generate hydrogen, establish an efficient hydrogen evolution system, effectively expand the light absorption range, and enhance the photocatalytic properties.
[0006] In order to achieve the above object, the technical solution of the present invention is as follows: The first technical purpose of the present invention is to provide a core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich anions on the surface. The composite catalyst material with a core-shell structure with rich anions on the surface is formed by generating an amorphous Ni(OH)2 layer on the MOF surface. The composite catalyst is made of a nickel source compound and a metal organic framework material MOF.
[0007] Preferably, the nickel source compound is any one of nickel nitrate hexahydrate, nickel sulfate hexahydrate, nickel acetate tetrahydrate, nickel bromide and nickel iodide.
[0008] Preferably, the molar ratio of the nickel source compound to the metal organic framework material MOF is 1:0.17; The second technical purpose of the present invention is to provide a method for preparing a core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich anions on the surface, which is prepared by using methanol as a solvent to generate amorphous Ni(OH)2 on the surface of a metal organic framework material MOF, and specifically comprises the following steps: Step 1: Preparation of metal organic framework MOF material NH2-MIL-125 Place isopropyl titanate, 2-aminoterephthalic acid, methanol and N,N-dimethylformamide in a reactor and mix them evenly. Set the reaction temperature to 150 °C and the reaction time to 16 h. After the reaction, wash the yellow sample with methanol and N,N-dimethylformamide several times and dry it naturally to obtain the metal organic framework MOF material NH2-MIL-125.
[0009] Step 2: Preparation of core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with anion-rich surface In a 100 mL reactor, 120 mg of the metal organic framework MOF material NH2-MIL-125 prepared in step 1 and different masses of nickel source compounds were added. Finally, 30 mL of methanol was added to the reactor. The mixture was ultrasonicated for 5 min. The reactor was heated to 120 ℃. After heating for 1 h, a core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst powder sample with rich anions on the surface was obtained.
[0010] Step 3: Wash and dry The core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst powder with rich anions on its surface prepared in step 2 is washed with anhydrous ethanol for multiple times, and then the powder sample is naturally dried to obtain the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich anions on its surface.
[0011] Preferably, the molar ratio of isopropyl titanate, 2-aminoterephthalic acid, methanol and N,N-dimethylformamide in step 1 is 15:30:3086:1621.
[0012] Preferably, the mass ratio of the metal organic framework material NH2-MIL-125 and the solvent methanol described in step 2 is 1:0.19.
[0013] Another object of the present invention is to provide an application of the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich anions on its surface in photocatalytic decomposition of water to generate hydrogen.
[0014] 1. The core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich anions on the surface of the present invention is prepared by hydrolyzing a nickel source compound on the surface of the metal organic framework material MOF to generate amorphous Ni(OH)2. During the reaction, Ni 2+ The hydrolysis caused slight etching of NH2-MIL-125, and the generated Ni(OH)2 gradually deposited on it to form a core-shell structure. Thanks to the formation of defects and the use of Ni(OH)2 as a co-catalyst, the migration of photogenerated carriers in the composite photocatalyst was enhanced, thereby improving the photocatalytic performance. Under 3 h of illumination, the optimal hydrogen evolution amount was 807.39 µmol g -1 .
[0015] 2. The core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich anions on its surface can be reused, and the amount of hydrogen evolution can be retained to 75.0% of the first time after four cycles of use.
[0016] 3. The preparation method of the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich anions on its surface is mild and simple. Compared with the traditional process of adding precious metal co-catalysts, the method is simple, low-cost, controllable and easy to operate, and the photocatalyst has strong stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is an X-ray diffraction pattern of the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with different anions on the surface in the present invention; Figure 2 This is a scanning electron microscope of the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst having sulfate ions on the surface prepared in Example 2 of the present invention; Figure 3 This is a transmission electron microscope of the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with sulfate ions on the surface prepared in Example 2 of the present invention; Figure 4 This is a line graph of hydrogen production of the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst having sulfate ions on the surface prepared in Example 2 of the present invention; Figure 5 This is a hydrogen production cycle diagram of the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst having sulfate ions on the surface prepared in Example 2 of the present invention; Figure 6 A histogram of hydrogen production of the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst prepared in Examples 1 to 5 of the present invention, the surfaces of which have acetate ions, sulfate ions, nitrate ions, bromide ions and iodide ions, respectively; Figure 7 The electrochemical impedance diagram of the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst prepared in Examples 1 to 5 of the present invention, the surfaces of which have acetate ions, sulfate ions, nitrate ions, bromide ions and iodide ions, respectively; Figure 8 This is a diagram of hydrogen production of the NH2-MIL-125 of the present invention and the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with sulfate ions on the surface. DETAILED DESCRIPTION
[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0019] Step 1: Preparation of metal organic framework MOF material NH2-MIL-125 445 µL of isopropyl titanate, 543.5 mg of 2-aminoterephthalic acid, 12.5 mL of methanol and 12.5 mL of N,N-dimethylformamide were placed in a reactor and mixed evenly. The reaction temperature was set to 150 ℃ and the reaction time was 16 h. After the reaction, the yellow sample was washed several times with methanol and N,N-dimethylformamide and dried naturally to obtain the metal organic framework MOF material NH2-MIL-125.
[0020] Step 2: Preparation of core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with anion-rich surface In a 100 mL reactor, add 120 mg of the metal organic framework MOF material NH2-MIL-125 prepared in step 1 and 122.3 mg of nickel nitrate hexahydrate, then add 30 mL of methanol to the reactor, ultrasonicate the mixture for 5 minutes, and disperse it evenly to obtain a precursor solution. Heat the reactor to 120 ° C, and after heating for 1 hour, the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst powder sample with rich anions on the surface is obtained.
[0021] Step 3: Wash and dry The core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst powder with rich anions on its surface prepared in step 2 is washed with anhydrous ethanol for multiple times, and then the powder sample is naturally dried to obtain the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich anions on its surface. Example 2
[0022] Step 1: Preparation of metal organic framework MOF material NH2-MIL-125 The preparation process of this step is the same as that of Example 1.
[0023] Step 2: Preparation of core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with anion-rich surface In a 100 mL reactor, 120 mg of the metal organic framework MOF material NH2-MIL-125 prepared in step 1 and 110.6 mg of nickel sulfate hexahydrate were added, and then 30 mL of methanol was added to the reactor. The mixture was ultrasonicated for 5 minutes and dispersed evenly to obtain a precursor solution. The reactor was heated to 120 ° C for 1 h to obtain a core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst powder sample with rich anions on the surface.
[0024] Step 3: Wash and dry The preparation process of this step is the same as that of Example 1. Example 3
[0025] Step 1: Preparation of metal organic framework MOF material NH2-MIL-125 The preparation process of this step is the same as that of Example 1.
[0026] Step 2: Preparation of core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with anion-rich surface In a 100 mL reactor, 120 mg of the metal organic framework MOF material NH2-MIL-125 prepared in step 1 and 104.7 mg of nickel acetate tetrahydrate were added, and then 30 mL of methanol was added to the reactor. The mixture was ultrasonicated for 5 minutes and dispersed evenly to obtain a precursor solution. The reactor was heated to 120 ° C for 1 h to obtain a core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst powder sample with rich anions on the surface.
[0027] Step 3: Wash and dry The preparation process of this step is the same as that of Example 1. Example 4
[0028] Step 1: Preparation of metal organic framework MOF material NH2-MIL-125 The preparation process of this step is the same as that of Example 1.
[0029] Step 2: Preparation of core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with anion-rich surface In a 100 mL reactor, 120 mg of the metal organic framework MOF material NH2-MIL-125 prepared in step 1 and 91.9 mg of nickel bromide were added, and then 30 mL of methanol was added to the reactor. The mixture was ultrasonicated for 5 min and dispersed evenly to obtain a precursor solution. The reactor was heated to 120 ° C for 1 h to obtain a core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst powder sample with rich anions on the surface.
[0030] Step 3: Wash and dry The preparation process of this step is the same as that of Example 1. Example 5
[0031] Step 1: Preparation of metal organic framework MOF material NH2-MIL-125 The preparation process of this step is the same as that of Example 1.
[0032] Step 2: Preparation of core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with anion-rich surface In a 100 mL reactor, 120 mg of the metal organic framework MOF material NH2-MIL-125 prepared in step 1 and 131.5 mg of nickel iodide were added, and then 30 mL of methanol was added to the reactor. The mixture was ultrasonicated for 5 min and dispersed evenly to obtain a precursor solution. The reactor was heated to 120 ° C for 1 h to obtain a core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst powder sample with rich anions on the surface.
[0033] Step 3: Wash and dry The preparation process of this step is the same as that of Example 1.
[0034] (1) Photocatalytic water decomposition for 3h hydrogen evolution test The performance of photocatalytic water decomposition to hydrogen under the same time and light intensity was tested using the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich anions on the surface prepared in Examples 1 to 5 and the original NH2-MIL-125 catalyst alone as a comparative example. The test results are shown in Table 1.
[0035] Table 1 Test results of hydrogen evolution performance of photocatalytic water splitting for 3h project Embodiment 1 Embodiment 2 Embodiment 3 Embodiment 4 Embodiment 5 Comparative Example <![CDATA[Hydrogen evolution amount by photocatalytic water splitting for 3 h, µmol g -1 > 591.85 807.39 257.18 462.38 131.11 200.35 The above-mentioned photocatalytic water splitting 3h hydrogen evolution performance test results show that the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich anions on its surface has an optimal hydrogen evolution capacity of 807.39 µmol g under 3 h illumination. -1 , the best hydrogen evolution efficiency is 4 times that of the original NH2-MIL-125.
[0036] (2) Repeated use cycle test Cyclic test method: First, take 10 mg of surface rich in SO4 2- The core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst sample powder was placed in a vial, and 5 mL of acetonitrile, 1 mL of triethanolamine, and 0.5 mL of water were added. After the above operation was completed, the vial was evacuated for 30 min. Then, the internal vacuum vial was illuminated (xenon lamp, 566.87 mW / cm 2 ), extract 1 mL of the newly generated gas in the bottle every 1 hour and analyze it in a gas chromatograph (Shimadzu GC-2014), and the reaction time is 3 hours. After the reaction is completed, repeat the experiment according to the above steps. In this repeated process, only 0.2 mL of triethanolamine is added in the last time. The results of cyclic hydrogen evolution are shown in Table 2.
[0037] Table 2 Four-cycle hydrogen evolution performance test results project First cycle Second cycle Third cycle Fourth cycle <![CDATA[Hydrogen evolution amount by photocatalytic water splitting for 3 h, µmol g -1 > 807.395 695.119 702.352 605.606 From the above four-cycle hydrogen evolution performance test results, it can be seen that the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich anions on the surface of the present invention can be reused, and the hydrogen evolution amount can be retained to 75.0% of the first time after four cycles of use.
[0038] In summary, the surface anion-rich core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst of the present invention has an optimal hydrogen evolution capacity of 807.39 µmol g under 3 h illumination. -1 , the best hydrogen evolution efficiency is 4 times that of the original NH2-MIL-125.
[0039] The catalyst can be recycled and reused, and after four cycles of use, the amount of hydrogen evolution can be retained to 75.0% of the first cycle. The composite catalyst can achieve efficient hydrogen evolution in a photocatalytic system.
[0040] What is described above is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich anions on its surface, characterized in that: The composite catalyst material is a core-shell structure with rich anions on the surface formed by generating an amorphous Ni(OH)2 layer on the surface of MOF. The composite catalyst is prepared from a nickel source compound and a metal organic framework material MOF.
2. The core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich surface anions according to claim 1, characterized in that: The nickel source compound is any one of nickel nitrate hexahydrate, nickel sulfate hexahydrate, nickel acetate tetrahydrate, nickel bromide and nickel iodide.
3. The core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich surface anions according to claim 1, characterized in that: The molar ratio of the nickel source compound to the metal organic framework material MOF is 1:0.
17.
4. A method for preparing the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich surface anions as claimed in claim 1, characterized in that: The method is prepared by using methanol as solvent to prepare an amorphous Ni(OH)2 layer on the surface of a metal organic framework material MOF.
5. The method for preparing a core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst having a surface rich in anions according to claim 4, characterized in that The steps include: Step 1: Preparation of metal organic framework MOF material NH2-MIL-125 The isopropyl titanate, 2-aminoterephthalic acid, methanol and N,N-dimethylformamide in a certain proportion were placed in a reactor and mixed evenly for reaction at a temperature of 150 °C for 16 h. After the reaction, the yellow sample was washed with methanol and N,N-dimethylformamide for several times and dried naturally to obtain the metal organic framework MOF material NH2-MIL-125. Step 2: Preparation of core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with anion-rich surface In a 100 mL reactor, 120 mg of the metal organic framework MOF material NH2-MIL-125 prepared in step 1 and different masses of nickel source compounds were added, and then 30 mL of methanol was added to the reactor. The mixture was ultrasonicated for 5 min, and the reactor was heated to 120 ℃. After heating for 1 h, the reaction was carried out to obtain a powdery surface anion-rich core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst.
6. The method for preparing a core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich surface anions according to claim 5, characterized in that: The molar ratio of isopropyl titanate, 2-aminoterephthalic acid, methanol and N,N-dimethylformamide described in step 1 is 15:30:3086:1621.
7. The method for preparing a core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich surface anions according to claim 5, characterized in that: The mass ratio of the metal organic framework material NH2-MIL-125 and the solvent methanol described in step 2 is 1:0.
19.
8. The method for preparing a core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich surface anions according to claim 5, characterized in that: The method also includes washing the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst powder with rich anions on the surface obtained in step 2 with anhydrous ethanol for multiple times and then drying it naturally.
9. Use of the core-shell NH2-MIL-125@Ni(OH)2 composite photocatalyst with rich surface anions as claimed in any one of claims 1 to 8 in photocatalytic decomposition of water to generate hydrogen.
Citation Information
Patent Citations
Preparation method and application of core-shell structure TiO2at-NH2-MIL-125 photocatalyst
CN117205968A